An experimental investigation of Quench Polish Quench (QPQ) coating on AISI 4150 steel. (1st December 2022) - Boopathi, Sampath
Abstract: In this research, the hardness, layer thickness, and corrosion rate of the nitro-carburizing coating on AISI 4150 steel using the Quench-Polish-Quench (QPQ) process have been investigated. Nitro-carburizing temperature (T), nitro-carburizing time (tc), and oxidation time (to) are considered coating parameters. The experiments were designed and analyzed to investigate the effects of coating parameters on responses by the Taguchi method. A 590 °C temperature of the nitro-carburizing solution and a 145 min duration of both the nitro-carburizing and oxidizing processes have been predicted to obtain the maximum micro-hardness (504.71 HV) and coating-layer thickness (13.60 μ m). A 570 °C temperature of the nitro-carburizing solution with the same process time is predicted to obtain the lowest corrosion rate (1.27 mm/miles). The optimum parameters set are used to perform Scanning electron microscopy (SEM), x-ray diffraction (XRD), and Energy-Dispersive x-ray Spectroscopy (EDS) analyses.